STRENGTHENING STUDENT CHARACTER THROUGH PBL: CHALLENGES IN PANCASILA PROFILE IMPLEMENTATION - Widiawati, Lilis; Rostini, Deti (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to explore the implementation of project-based learning in strengthening students' character and identify the challenges faced in the context of the Pancasila Student Profile Project (P5) at SDN 156 Pasirkaliki and SDN Leuwidulang. The research approach used is qualitative with mixed methods through in-depth interviews, participatory observation, and documentation. Data were collected from teachers, students, and parents to thoroughly understand the dynamics of project-based learning implementation in the two primary schools. The results show that project-based learning can strengthen students' character in the aspects of discipline, responsibility, cooperation, independence, and leadership. Students become more active, confident, and show increased critical thinking skills. However, the implementation of project-based learning also faces a number of challenges, including limited teacher training, lack of infrastructure, variations in student readiness, and minimal parental and community involvement. These challenges impacted the effectiveness and consistency of the character project implementation. The discussion highlighted that the project-based learning model is effective as an integrative learning tool between academic and character values. Mentoring strategies and cross-party collaboration are needed to ensure the sustainability and expansion of impact. In conclusion, project-based learning has potential as a strategic pedagogical approach in contextualised and applicable character education in Indonesian primary schools.